Normative examination of the considerations of pre-trial judge on distortion of the value of the instruments of evidence - Fadlan Fadlan; Apridony Apridony (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
Currently there is a pretrial decission No.5/Pid.Pre/2018/PN BTM which cancels the determination of the suspect with the consideration that the evidence for the determination of the suspect has been distorted by the investigation period which is considered too long, it’s necessary to analyze the construction flow of the judge's legal considerations and normative juridical examination as well as the legal consequences of the decission against the investigator. This research used descriptive analytical method using a normative approach (legal research) to obtain secondary data and an empirical approach (juridical sociological) to obtain primary data through observation (observation). The results showed that pretrial judges form a new legal method regarding the distorted value of evidence based on the period of investigation in which this consideration was no longer on the assessment of formal aspects, from this decission Investigators if they want to re-determine someone as a suspect must use two different pieces of new evidence. For this reason, the Supreme Court is expected to establish special rules regarding mechanisms and clear boundaries for pretrial judges in establishing the rule of law, besides that a clear definition of deviant and/or fundamentally deviant decissions is needed and the annulling mechanism to anticipate legal smuggling.